2003
DOI: 10.2460/ajvr.2003.64.1099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasonographic characteristics of the gastroduodenal junction during pyloroplasty performed laparoscopically or via conventional abdominal surgery in dogs

Abstract: Analysis of results of this study suggests that ultrasonography is useful for detecting relevant morphologic changes in the pyloric sphincter after pyloroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Future investigations should identify the ideal technique Our previous studies demonstrated that laparoscopic Finney pyloroplasty is technically more demanding than Heineke-Mikulicz pyloroplasty or Ramstedt pyloromyotomy [12,13], but allows for a greater increase in pyloric diameter [11]. As this report shows, mechanical suturing has markedly simplified the gastroduodenal anastomosis.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Future investigations should identify the ideal technique Our previous studies demonstrated that laparoscopic Finney pyloroplasty is technically more demanding than Heineke-Mikulicz pyloroplasty or Ramstedt pyloromyotomy [12,13], but allows for a greater increase in pyloric diameter [11]. As this report shows, mechanical suturing has markedly simplified the gastroduodenal anastomosis.…”
Section: Discussionmentioning
confidence: 69%
“…As in our previous studies [12,13], we performed fluoroscopic and ultrasonographic studies to determine the efficacy of the laparoscopic procedures. In both groups, the gastric emptying time was increased after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure, with an open approach, is in fact undertaken in cases of benign GOO, and is only rarely performed in the emergency setting since it is more technically challenging than the Heineke-Mikulicz pyloroplasty (20)(21)(22)(23). FP can be used particularly when the site of the perforation is too wide and located in D2, to ensure good caliber of the pylorus when no healthy tissue around the ulcer can provide good closure of the duodenal defect (18,24). As this is a single case report, further studies are required to define the long-term outcomes and/or compare LS to open surgery in perforated DU with GOO.…”
Section: Discussionmentioning
confidence: 99%